Translation of Humor and Culture: Examples from The Big Bang Theory - Téllez Quirós, Jared (2024)
Translation of humor and cultural references are the main challenges that linguists focused on audiovisual translation must overcome. The objective is to translate the source material into something that the audience will understand. Not all comical situations and expressions or cultural allusions are translatable literally or have an equivalent in the target language. To maintain the same level of impact and comic relief, these professionals make important decisions that range from omission to a complete transformation of each joke and reference. This paper contains an analysis of the translations into Spanish of four heavily charged instances of comedy and cultural references of the television series The Big Bang Theory.